(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Between 2015 and 2050, the World Health Organization predicts that the number of old people would quickly increase. Population ageing is leading to an increase in physical disabilities and mobility issues. There is a significant opportunity to improve healthcare delivery by using assistive robots, which are constantly improving robotic technology. Robotic technologies for the care of the elderly and handicapped are thus becoming more relevant. In an assistive robotic system, a sensor glove for human-robot interaction is conceived, manufactured, and assessed in this article. Flex sensors and an inertial measurement unit (IMU) are used to detect the user’s finger motions and additional off-the-shelf electrical components are employed in the sensor glove. It is the primary objective of this study to make human-assistive robot interaction more intuitive and dependable. As a result, this study focuses on three key topics: 1) developing a pattern for these kinds of sensor gloves, 2) testing the performance of sensor gloves with the use of flexible sensors, and 3) examining how to analyse systems with a person in the loop while using a sensor glove. Using this design pattern, the sensor glove can be a reliable interface for operating the assistive robotic system, according to our experiments. Aside from that, our estimate approach may be used to the study of an assistive robotic system with a person in the loop, allowing us to theorise about the system’s optimal parameters.